Effects of various dietary levels of copper hydroxychloride on growth performance and tissue response in Pacific white shrimp Litopenaeus vannamei fed practical diets. (19th December 2015) - Zhou, Y.; Rhodes, M.A.; Liu, J.; Davis, D.A.
Abstract: Two trials were conducted to evaluate the performance of Pacific white shrimp Litopenaeus vannamei offered diets containing various copper (Cu) levels from Cu hydroxychloride (Cu2 (OH)3 Cl) containing 58.81% copper in the clear water recirculating system. In both trials, the basal diet (360 g kg −1 protein, 80 g kg −1 lipid) containing approximately 10 mg Cu kg −1 was primarily comprised of fishmeal, soybean meal, corn protein concentrate and whole wheat. In trial 1, test diets were produced supplementing the basal diet with 5, 10, 20, 40 and 60 mg Cu kg −1 from Cu hydroxychloride. Four replicate groups of 15 shrimp per tank (initial weight 0.28 g) were offered diets in slight excess over 8 weeks. In trial 2, the basal diet was supplemented with 30, 90, 150, 210 and 270 mg Cu kg −1 from Cu hydroxychloride. Seven replicate groups of 15 shrimp per tank (initial weight 0.22 g) were offered feed in slight excess over 7 weeks. At the end of the two growth trials, no significant differences were observed in final biomass, final mean weight, percentage weight gain, feed conversion ratio (FCR) and survival. In trial 1, the Cu concentrations of the carapace, hepatopancreas and whole shrimp linearly increased with increasing dietary Cu supplements. In trial 2, polynomial regression of Cu concentrations of the carapace, hepatopancreas and whole shrimp against analysed dietary Cu content indicated that a plateau was reached at 215 mg analysed Cu kg −1 . Results of this study indicate that there was no negative effect of high levels of Cu supplement with regard to growth and survival. Tissue levels generally increased up to around 200 mg Cu kg −1 diet and then decreased, possibly indicating a shift in physiology.